Disease, Demon, and the Deity: Case of Corona Mātā and Coronāsur in India - Yadav, Megha (Religions, 2022)
As India faced multiple waves of the pandemic, religious responses arose to accommodate and make sense of the situation. In the face of uncertainty, disease and death, people turn not just towards the medical sciences but also religion. The emergence of a new Hindu goddess, Corona Mātā/Coronavirus Mardhinī encapsulates people’s fear, faith, and devotion. Although the goddess is new, the tradition of disease goddesses is ancient. The Indian Subcontinent has a long history of mother goddesses who have been protecting their devotees from diseases such as smallpox, fever, plague, etc. This paper attempts to examine the emergence of Corona Mātā in the historical context of these ‘protective mothers’. On one hand, historically, these goddesses have emerged as a result of interaction between Brahmanical religion and regional practices. On the other hand, these disease-centred goddesses can also be seen as the result of fear and faith. This paper will analyse the location of Corona Mātā in the ever-evolving pantheon of Hindu deities in the context of a 21st-century pandemic.